A retrospective analysis of children with and without disabilities attending the Teddy Bear Clinic, Johannesburg - Deroukakis, Marilena (My University, 2010)
The intersection of two marginalised groups of children, the disabled and the abused, was the focus of this research report. The study examined data from the Teddy Bear Clinic over an eight-year period and detected differences in the prevalence of sexual abuse, physical abuse and neglect of disabled and non-disabled children. The population of disabled-abused were further classified according to age, population group and gender in order to elucidate relationships between variables that might affect prevalence of maltreatment. A summary of the results shows that specific sub-populations of the disabled (the physically, mentally and learning disabled) had prevalence rates peculiar to them. The mentally and physically disabled had increased rates of sexual abuse, whilst the learning disabled had increased prevalence for neglect. Analysis of those children with multiple disabilities revealed no risk for neglect but they were at increased risk for sexual abuse. Disabled children are therefore not a homogeneous group.
MSc (Med) (Paediatric Neurodevelopment), Faculty of Health Sciences, University of the Witwatersrand
Keywords: disabled children; sexually abused children; neglected children